2016
DOI: 10.1177/0194599816629379
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Esophagram versus High‐Resolution Manometry in the Detection of Esophageal Dysmotility

Abstract: Esophagram is useful in the assessment of anatomic abnormalities but is a poor screening examination for the detection of esophageal dysmotility. Patients with suspected esophageal dysphagia should be referred for HRM to evaluate motility disorders and identify potential treatment targets, regardless of esophagram results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…Good concordance between barium and manometry for the diagnosis of achalasia was also reported by Anumandla et al [16]. Our radiographic sensitivity was relatively higher compared to some other studies such as O'Rourke et al reported a very low sensitivity of barium swallow (29%) for diagnosis of achalasia [17]. Whereas Howard et al reported that radiographic findings were consistent with the manometric diagnosis of achalasia in 45% patients [18].…”
Section: Discussionsupporting
confidence: 81%
“…Good concordance between barium and manometry for the diagnosis of achalasia was also reported by Anumandla et al [16]. Our radiographic sensitivity was relatively higher compared to some other studies such as O'Rourke et al reported a very low sensitivity of barium swallow (29%) for diagnosis of achalasia [17]. Whereas Howard et al reported that radiographic findings were consistent with the manometric diagnosis of achalasia in 45% patients [18].…”
Section: Discussionsupporting
confidence: 81%
“…In two studies, the diagnostic values of imaging techniques were compared to manometry 10,11 . The results of these two studies lend some support to the notion that manometry rather than imaging is the gold standard for the diagnosis of achalasia.…”
Section: Achalasia Diagnosismentioning
confidence: 96%
“…It is also recommended that the esophagus is included in the fluoroscopic assessment of the pharynx as carried out by speech pathologists. [28][29][30][31] Such evaluation has been shown to have 63% sensitivity and 100% specificity for esophageal abnormalities. 30 This does not replace a formal esophagogram if indicated.…”
Section: The Oropharyngeal Assessmentmentioning
confidence: 99%
“…23 A fluoroscopic examination is less sensitive to dysmotility than manometric investigations and, therefore, if there is suspicion of motility problems, pharyngoesophageal manometry is indicated. 31 Currently available esophageal investigations are often complementary, and a combination of investigations may be required to achieve an accurate diagnosis. This needs to be tailored to a patient's degree of concern, functional impact, and existing risk factors.…”
Section: The Oropharyngeal Assessmentmentioning
confidence: 99%
See 1 more Smart Citation